Tanks fight on the town square in Mykolaiv on the Dniester river on the first day of July 1941 - Voitovych, Leontiy (City and War, 2021)
The article shows some of the causes of the defeat of the Soviet army at the beginning of the Soviet-German war, based on one of the tanks clashes on the city square in Nikolaev on the Dniester. The circumstances of this clash are partly known, thanks to the preserved German photos. The text attempts to explain how the German 101st Light Infantry Division, which did not include any tanks, could defeat the Soviet units equipped with the then most powerful KW-1 and KW-2 tanks. The reasons for the mistakes of the Soviet command were also analyzed, as they were unable to determine the directions of the enemy’s main strikes and could not organize an effective defense, having an advantage, both in man and military equipment. In this context, one can clearly see the heroism of ordinary Soviet soldiers who fought to the end. Particular attention was paid in the text to the specificity of tanks combat in urbanized area, in which the Germans managed to destroy the KW-1 heavy tanks, which were difficult to destroy even with the famous 88 mm anti-aircraft gun – in this case, the German soldiers managed to destroy them with a light anti-tank gun caliber 28 mm.